Strain Fidelity of Chronic Wasting Disease upon Murine Adaptation - Sigurdson, Christina J. (American Society for Microbiology, 2006)
Chronic wasting disease (CWD), a prion disease of deer and elk, is highly prevalent in some regions of North America. The establishment of mouse-adapted CWD prions has proven difficult due to the strong species barrier between mice and deer. Here we report the efficient transmission of CWD to transgenic mice overexpressing murine PrP. All mice developed disease 500 ± 62 days after intracerebral CWD challenge. The incubation period decreased to 228 ± 103 days on secondary passage and to 162 ± 6 days on tertiary passage. Mice developed very large, radially structured cerebral amyloid plaques similar to those of CWD-infected deer and elk. PrP(Sc) was detected in spleen, indicating that murine CWD was lymphotropic. PrP(Sc) glycoform profiles maintained a predominantly diglycosylated PrP pattern, as seen with CWD in deer and elk, across all passages. Therefore, all pathological, biochemical, and histological strain characteristics of CWD appear to persist upon repetitive serial passage through mice. These findings indicate that the salient strain-specific properties of CWD are encoded by agent-intrinsic components rather than by host factors.